Correlations Between Structures of Expanded Graphite – Polymer Composites and Acoustic Emission Phenomena / Korelacje Pomiędzy Strukturą Kompozytów Grafit Ekspandowany-Polimer A Zjawiskami Emisji Akustycznej - Berdowska, A.; Berdowski, J.; Aubry, F. (Archives of metallurgy and materials, 2015)
Compressed expanded graphite was applied as a base matrix to the preparation of microporous composites as products of impregnation, polymerization and carbonization of poly-furfuryl alcohol. During carbonization, the original polymeric structure is transformed into an amorphous turbostratic carbon structure with ultramicropores. The structure, porosity and many chemical and physical properties change after each stage of their technological treatment. The acoustic emission method was used for accurate determination of these changes. It is possible to determine a large number of acoustic emission parameters and therefore to increase the amount of information provided by the studied materials. Acoustic emission pulses, counts rate, events rate, signal peak value and their sums were measured. Also frequency spectrum was received as a result of acoustic emission signal analysis with use of Fourier transformation procedure. The conclusions resulting from the Fourier analysis of the registered spectrum are very interesting and provide information about composite structures as well as bonds between the graphite matrix and the polymer that fills it. Analysis of acoustic emission parameters provides data on physical and chemical processes that would be very difficult to study by means of other techniques. Wide applications of these porous composites make them very interesting subject of the study.